Mechanism of the selective reduction of nitrogen monoxide on platinum-based catalysts in the presence of excess oxygen - Burch, R.; Millington, P.J.; Walker, A.P. (Applied catalysis. B, Environmental, 1994)
A range of alumina-supported platinum catalysts have been prepared and investigated for the selective reduction of nitrogen monoxide in the presence of a large excess of oxygen. Steady-state microreactor experiments have demonstrated that these catalysts are very active and selective for the reduction of nitrogen monoxide by propene at temperatures as low as 200°C. There does not appear to be a simple correlation between the activity for nitrogen monoxide reduction and the platinum surface area. Instead it is found that there is a very good inverse correlation between the maximum nitrogen monoxide reduction activity and the temperature. The most active catalysts for selective nitrogen monoxide reduction are those that generate activity at the lowest temperature. The technique of temporal analysis of products (TAP) has been used to obtain detailed mechanistic data about the selective nitrogen monoxide reduction reaction on an alumina-supported platinum catalyst. Using carbon monoxide, hydrogen or propene as reductant it has been demonstrated that the predominant mechanism for selective nitrogen monoxide reduction involves the decomposition of nitrogen monoxide on reduced platinum metal sites, followed by the regeneration of the active platinum sites by the reductant. In the decomposition step it has been shown that oxygen from nitrogen monoxide is retained on the surface of the platinum and blocks the surface for further adsorption/reaction of nitrogen monoxide; it has been observed that oxidised platinum catalysts are not active for the nitrogen monoxide reduction reaction. Under typical operating conditions, propene is a far more efficient reductant than either carbon monoxide or hydrogen. The greater efficiency of propene as a reductant is explained on the basis of the additional reducing power of the propene molecule, which can react with as many as nine adsorbed oxygen atoms, ensuring that 'patches' of reduced platinum are available for nitrogen monoxide adsorption/reaction. A small additional activity of reduced platinum in the presence of propene, which is not observed when carbon monoxide or hydrogen is used as reductant, has been explained on the basis of a second mechanism involving the carbon-assisted decomposition of nitrogen monoxide at sites on the reduced platinum adjacent to adsorbed carbon-containing moieties, believed to be fragments from adsorbed propene molecules. A model for the selective reduction of nitrogen monoxide on alumina-supported platinum catalysts is presented which is capable of explaining all the results obtained in this work and in the published literature on this subject.